Numerical simulations of vortex ring leapfrogging - Gao, Zijian (2017)
This paper reports upon a numerical study on the leapfrogging of two elliptical vortex rings at Re=2200 and Re=4400. To start with, a single circular vortex ring model is developed and tested using Large Eddy Simulation in Ansys Fluent. A second model of two circular vortex rings leapfrogging is developed and simulated at Re=3000. Its results are compared with published simulation and experimental results to validate the leapfrogging behavior of the model. A single elliptical vortex ring model is developed as the third model. A simulation on single elliptical vortex ring of Aspect Ratio 3 at Re=2189 is conducted and compared to published simulation results to validate the axis switching behavior of the model. Finally, simulations of two elliptical vortex rings leapfrogging at Re=2200 and Re=4400 are conducted. Bifurcation is observed in both Reynolds numbers where the trailing ring is bifurcated into three rings. Two of these bifurcated rings at the sides collide and combine with the leading ring. The centre bifurcated ring reduced in size and travelled through the leading ring. Only one leapfrogging is possible with elliptical vortex rings at a separation distance of R0 independent of Reynolds number.